The impact of medicines shortages on pharmaceutical practice - Alin-Viorel Focsa; Magdalena Birsan; Maria Dragan; Ruxandra Teodora Stan; Cornelia Mircea; Catalina Daniela Stan (Amaltea Medical Publishing House, 2022)
Access to medicines is a fundamental human right and is a vital element of health care. Over the last 10 years, there has been a tendency for the global discontinuation of drug supply to become a major problem, with an increasing exacerbation of this phenomenon in the European Union, with a potential negative impact on patient health care due to multiple causes (manufacturing problems, drug pricing policy, parallel export etc.). National Agency for Medicines and Medical Devices of Romania (NAMMDR) argues, in full agreement with European Medicines Agency, that in this situation effective collaboration between the various stakeholders and regulators is required, and also a good communication between manufacturers, distributors and authorities. It is a point of view that NAMMDR supported in the working meetings with the representatives of the marketing authorization holders/ manufacturers, wholesale distribution, patient associations. According to pharmacists, situations have been reported in which patients tend to stock up on medicines, and this puts additional pressure on existing stocks. In this work, we intended to draw attention to the medicine shortages issue which has a huge impact on national health systems, on patients' safety, on public health and healthcare professionals.